If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + -20 = -3 Reorder the terms: -20 + 4s = -3 Solving -20 + 4s = -3 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4s = -3 + 20 Combine like terms: -20 + 20 = 0 0 + 4s = -3 + 20 4s = -3 + 20 Combine like terms: -3 + 20 = 17 4s = 17 Divide each side by '4'. s = 4.25 Simplifying s = 4.25
| 6x+2=-6+6x | | 3x-6=2x+5(x-1) | | 3x-12=-36 | | 3(2x-1)-(x-4)=2 | | .5(4x-10)+5=x-11 | | -4=4-u/2 | | 6x-3=7x+4 | | 6x+12=4x-18 | | x^3+x^2*y-4*y^2=0 | | 7b-21-8b=2 | | 10+3-6+34= | | 4(x+2)-17=35 | | 3x^2-5x-4-6x+8-x^2= | | -2x=-10-2x | | 2xy+4z-7xy-7z= | | 3r=30r+21 | | 10x=2x+26 | | -3xy+2x-7z= | | 5/8=2m+3/8 | | 5(3n+1)=2(5n-4)+6n | | 7x-8+4=5x-2 | | (8w)(2w^9y^7)(3y^8)= | | 2(u+3v)=4(y-5) | | 7-x+3=9x+10 | | -4-2y+3-y= | | 4y-14-13-y=-9+15 | | 3rs-6r+3s-7rs+10r-3s= | | 7x+9+8x-4= | | G=5g+5u | | 8x+1=-x-1 | | 9x+10x= | | 2y^2-8y+15-13y^2-8y+1= |